Root canal retreatment followed by apicoectomy and direct restoration with intracanal retention on overfilling obturation - Damayanti, Asri; Karima, Aftina Mutiara; Widyastuti, Andina; Untara, Raphael Tri Endra (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
The success of endodontic treatment depends on proper shaping, disinfection, and obturation of the root canals. The filling material must adequately occupy the root canal space without extending the anatomical apex. Overfilling occurs when the filling material extrudes into the periapical tissues beyond the apex, which negatively affects the long-term prognosis. Endodontic overfilling cases can be addressed through surgical treatments aimed at preserving the tooth. This case report aims to inform to highlight endodontic surgery as an effective treatment for cases of failed root canal treatment due to overfilling of the obturation material. A 27-year-old male patient came to the Dental Conservation clinic at RSGM Prof. Soedomo with a chief complaint of the left maxillary lateral incisor, which had undergone discoloration and caused discomfort during chewing. The tooth had undergone root canal treatment two years prior. Periapical radiographic examination revealed that tooth 22 had been treated with overfilling obturation material and there was widening of the periodontal membrane in the periapical area. Root canal retreatment was performed using the crown-down preparation technique, followed by single-cone obturation with a bioceramic sealer. At the subsequent visit, an apicoectomy was performed, involving flap opening, alveolar bone exposure, removal of granulation tissue, and resection of 3 mm of the tooth apex. Retrograde filling with Mineral Trioxide Aggregate (MTA) was applied, followed by bone grafting and membrane placement. The area was sutured and covered with a periodontal dressing. The final restoration was completed using direct composite resin with intracanal retention. At the one-week follow-up, the patient reported no complaints. In conclusion, apicoectomy is an effective solution for overfilling cases. This case report demonstrates that surgery combined with retreatment can preserve the tooth and restore its function.